Identification of Cryptosporidium parvum in Stool Specimen Using Different Diagnostic Methods in Wasit Province/Iraq - Abdulsada A. Rahi; Salam M. Khlaif (Institute of Medico-legal Publications Pvt Ltd, 2021)
The present study aimed to investigate the presence and prevalence of Cryptosporidium amongimmunocompromised patients in Wasit Hospitals and health centers to determine the best method for itsdiagnosis. The study started from the 1st of August to the end of November 2020. One hundred forty stoolsamples were collected from immunocompromised patients from both genders who attended the hospitaland health centers at Wasit province. Stool samples were inspected by modified acid-fast stain as a standardmethod, enzyme linked immunosorbent assay (ELISA) and Molecular Nested PCR method. Modified Ziehl-Neelsen technique revealed 46 (33%) positive cases for Cryptosporidium oocysts, of 85 males and 55 females,highly significant relationship was found between the genders and between different age groups of infectionwith a highly significant difference between rural and urban area. The prevalence of Cryptosporidium was57.14% using nested PCR and 38.46% for ELISA in comparison with MZN method. It is concluded thatcryptosporidiosis found to be endemic in Wasit Province for the first time and the nested PCR was the mostreliable technique for its diagnosis.